Asiyah : Sang Mawar Gurun Fir aun / Sibel Eraslan ; penerjemah, Ahmad Saefudin, Hyunisa Rahmadia, Erwin putra ; penyunting, Bima - ERASLAN, Sibel; Ahmad Saefudin; Hyunisa Rahmanadia; Erwin Putra; Bima (Kaysa Media, 2014)
vi, 446 hlm. ; 20 cm . [3 eks.]